Counseling in Social Work Practices during the Covid-19 - Meiti Subardhini; Sakroni Sakroni (UIN Sunan Kalijaga Yogyakarta, 2021)
This study aims to describe the practice of counseling during the COVID-19 period, surveying several clients. This study was conducted using a qualitative method. With data collection techniques, namely interviews and documentation studies of several clients who had attended counseling during the COVID-19 pandemic. Some of the obstacles felt by the client, including: limited time, difficult to convey problems, not awake, network constraints, difficulty interpreting responses / difficult body language to read and so on. Likewise, counselors who provide services during the COVID-19 pandemic with distance counseling, there are several things that become obstacles, such as: obstacles in exploring problems due to limitations in interpreting the client's body language except through voice intonation, alternative choices of action / solutions are limited to technique. or short therapy / brief therapy etc. Therefore, the results of the researchers recommend that social workers in conducting long-distance counseling with the media pay attention to the following: 1) advantages and disadvantages in counseling services; 2) the use of technological assistance in the counseling service is courageous; 3) form of courageous counseling accuracy; 4) access to applications for courageous counseling services; 5) legal and regulatory aspects in the use of technology in counseling; 6) technical matters relating to technology in business and law if services are provided between regions or countries. Keywords: Remote Counseling, Social Work Practice, Covid-19 Penelitian ini bertujuan untuk menggambarkan praktik konseling pada masa COVID-19, survey terhadap beberapa orang klien. Kajian ini dilakukan dengan menggunakan metode kualitatif. Dengan teknik pengumpulan data yaitu dengan wawancara dan studi dokumetasi terhadap beberapa orang klien yang telah mengikuti konseling saat pandemi COVID-19. Beberapa hambatan yang dirasakan klien, diantaranya : waktu yang terbatas, sulit menyampaikan masalah, kekhawatiran kerahasiaan tidak terjaga, kendala jaringan, sulit mengartikan respon/ bahasa tubuh sulit terbaca dan lain sebagainya. Demikian halnya dengan konselor yang melakukan layanan dalam masa pandemi covid-19 dengan konseling jarak jauh ada beberapa hal yang menjadi kendala, seperti : hambatan dalam menggali masalah karena keterbatasan dalam memaknai bahasa tubuh klien kecuali lewat intonasi suara, pilihan alternatif tindakan / solusi terbatas pada teknik atau terapi singkat / brief therapy dll. Oleh sebab itu hasil peneliti merekomendasikan kepada pekerja sosial dalam melakukan konseling jarak jauh melalui media daring agar memperhatikan hal-hal berikut: 1) kelebihan dan kekurangan dalam layanan konseling daring; 2) penggunaan bantuan teknologi dalam layanan konseling daring; 3) ketepatan bentuk konseling daring; 4) akses terhadap aplikasi untuk layanan konseling daring; 5) aspek hukum dan aturan dalam penggunaan teknologi dalam konseling; 6) hal-hal teknis yang menyangkut teknologi dalam bisnis dan hukum jika seandainya layanan diberikan antar wilayah atau negara. Kata Kunci: Konseling jarak jauh, Praktik Pekerjaan Sosial, Covid-19